Moderating Effect of Foreign Capital Flow on Investor Sentiment and Stock Returns in ASEAN - Hadi Ahmad Sukardi; Nugraha Nugraha; Toni Heryana; Yayat Supriyatna (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: ASEAN capital markets exhibit persistent return volatility that is inconsistent with macroeconomic fundamentals, suggesting the influence of behavioral and structural factors beyond the Efficient Market Hypothesis (EMH). Objective: This study examines the direct effect of investor sentiment on stock returns across six ASEAN economies and tests the moderating role of foreign capital flows in this relationship. Methods: Using quarterly panel data from 2003 to 2024 (N = 504) covering Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam, this study employs moderated regression analysis within a fixed effects model (FEM). Investor sentiment is proxied by the Consumer Confidence Index (CCI), stock returns are measured using national composite indices, and foreign capital flows are operationalized through Foreign Direct Investment (FDI). The Hausman test confirmed FEM as the appropriate estimator. Results: Investor sentiment exerts a positive and significant effect on stock returns (β = 0.187, p < 0.05). Although FDI alone does not significantly predict returns (p = 0.177), the interaction term CCI × FDI is highly significant (β = 0.115, p < 0.01), confirming a catalytic moderating effect. Conclusion: Foreign capital inflows amplify the sentiment–return relationship in ASEAN markets. These findings offer critical insights for policymakers and portfolio managers regarding behavioral market dynamics and capital flow surveillance in emerging economies.